The Effect of Motivation, Work Facilities and Non-Physical Work Environment on the Performance of Village Officials at Tiru Kidul Village Office - Ayonda , Dhuta Noferescha Putra; Laksono , Sonny Subroto Maheri; Nadhiroh , Umi (Business and Investment Review, 2023)
The purpose of this study was to determine the motivation grower, work facilities and non-physical work environment on financial performance persial and simultaneously. This study uses multiple linear regression analysis with the help of SPSS software. The study was conducted quantitatively by processing the primary data in the form of observations and questionnaires that have been disseminated researchers. The object of research is all employees of the village office of 30 people. Sampling is taken by saturated Sampling. The results showed that Motivation, work facilities and non-physical work environment both simultaneously and partially managed to show a positive effect on the performance of the device at the Tiru Kidul Village Office statistical results showed all significant variables and passed the criteria of the T test and F test. As for the dominant effect obtained by the work facility by showing the largest beta results from other variables in the study.